2017
DOI: 10.1021/acsami.6b14942
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Cobalt Nanoparticles Interacting with Nitrogen-Doped Carbon Nanotube in Situ Generated from a Metal–Organic Framework for the Oxygen Reduction Reaction

Abstract: A metal organic framework (MOF), synthesized from cobalt salt, melamine (mela), and 1,4-dicarboxybezene (BDC), was used as precursor to prepare Co/CoN/N-CNT/C electrocatalyst via heat treatment at different temperature (700-900 °C) under nitrogen atmosphere. Crystallites size and microstrain in the 800 °C heat-treated sample (MOFs-800) were the lowest, whereas the stacking fault value was the highest among the rest of the homemade samples, as attested to by the Williamson-Hall analysis, hence assessing that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Additionally, concerning the binding energies of Co 2+ and Co 3+ , the corresponding shift trend is in the order CoO x /C‐600<CoO x /C‐500≈CoO x /C‐700 (cf. Table ), suggesting that the charge transfer between Co‐containing species and carbon matrix in CoO x /C‐600 is stronger than on the other samples, which probably leads to enhancement of ORR activity ,…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, concerning the binding energies of Co 2+ and Co 3+ , the corresponding shift trend is in the order CoO x /C‐600<CoO x /C‐500≈CoO x /C‐700 (cf. Table ), suggesting that the charge transfer between Co‐containing species and carbon matrix in CoO x /C‐600 is stronger than on the other samples, which probably leads to enhancement of ORR activity ,…”
Section: Resultsmentioning
confidence: 59%
“…The D‐band (1350 cm −1 ) and G‐band (1598 cm −1 ) are individually relevant to the disorder and the crystallinity degree of sp 2 carbon materials, respectively. The band deconvolution, as discussed in previous reports,, the I D /I G ratio values of ca. 1.12, 1.22 and 1.18 for CoO/C‐500, −600 and −700, respectively, indicate a more graphitic degree and a large disordered carbon domain in CoO x /C‐600 ,…”
Section: Resultsmentioning
confidence: 99%
“…[42,58,[70][71][72][73] Taking MIL-88B-NH 3 (Fe 3 O(H 2 N-BDC) 3 , H 2 N-BDC = 2-aminoterephtalic acid) for example, Zhao et al prepared well-defined N-doped carbonized nanoparticles (CNPs) by pyrolyzing spindle-like MIL-88B-NH 3 NPs. [42] Notably, unlike IM-based ligands in ZIFs, which already contain N atoms in pyridine/pyrrole configurations, H 2 N-BDC only contains amino-type N atoms.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
“…As an important alternative to Pt catalysts, MOF-derived materials exhibit remarkable ORR performance in terms of activity, durability, and tolerance to methanol. [24,[32][33][34][38][39][40][41][42][43][44]47,53,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][75][76][77]81,83,97,99,[107][108][109] In particular, some newly developed MOF derivatives achieved highly improved activity that is comparable and even superior to Pt catalysts under identical experimental conditions. Table 1 summarizes the catalytic performances of representative MOF-derived electrocatalysts for the ORR.…”
Section: Orrmentioning
confidence: 99%
“…These will provide porous architecture, electric conductivity, and rich catalytic active sites, which all help the catalytic performance for ORR. However, previous studies reported Co nanoparticles (NPs) electrocatalysts derived from MOFs have uniform size distribution ranging from 10 to 20 nm . As we know, the smaller particles show a better catalytic performance for ORR because they can provide more catalytic centers and active sites which promote a faster electron and mass transfer process .…”
Section: Introductionmentioning
confidence: 99%